Wensters new collegiate dictionary, / a Merriam -Webster - Webster, Merriam (1973)
Explanatory chart, notes, the english language and its history, abbreviations in this work, pronunciation symbols; dictionary of english languge, foreign words and phrases, biographical names, colleges and universities, signs and symbols, a handbook of style.